Effects of Physical Activity Programs on the Improvement of Dementia Symptom: A Meta-Analysis. (13th October 2016) - Lee, Han Suk; Park, Sun Wook; Park, Yoo Jung
Abstract : Objective . To confirm that physical activity program improves the symptoms of dementia and the most effective physical activity was selected to help establish exercise programs. Methods . Three databases, PubMed, Science Direct, and Willey online, were used to collect articles. The databases were published between January 2005 and December 2015. Keywords such as "dementia, " and "physical activity" were used in searching for papers. As a result, nine studies were selected in the second screening of the meta-analyses. Results . The improvement in the dementia symptom of physical capacity was 1.05 (high effect size, 95% CI: 0.03 to 0.73), ability of activity of daily living was 0.73 (slightly high effect size, 95% CI: 0.23 to 1.23), cognitive function was 0.46 (medium effect size, 95% CI: 0.26 to 0.66), and psychological state was 0.39 (lower than the medium effect size, 95% CI: 0.01 to 0.77). Conclusion . The physical activity for patients with dementia had an effect on the improvement of physical capacity and combined exercise was the most effective physical activity.